GENRE BASED APPROACH TO IMPROVE STUDENTS’ WRITING ABILITY OF TENTH GRADERS OF SENIOR HIGH SCHOOL - Lukmawardani, Nur Intan; Badriyah, Ima Mutholliatil (English Edu: Journal of English Teaching and Learning, 2022)
The purpose of this study is to portray the effect of Genre-Based Approach on the writing skills of tenth-grade high school students from three major islands in Indonesia; Sulawesi, Sumatra and Java. This study employs a qualitative research design, which describes the effectiveness of the genre-based approach on students' writing skills. The data collection technique used in this study is library research (literature study) where the data was collected from scientific journals and other publications that were worthy of being research sources. The results of this study indicate that the genre-based approach has a positive effect in improving students' abilities on several big islands in Indonesia (Sulawesi, Sumatra, and Java) as evidenced by pre-test to post-test results which have increased. The significant of this study is to add insight for readers about the effectiveness of the genre-based approach in teaching writing in senior high school levels especially in tenth grade